Bundle sheath ontogeny in Kranz and non-Kranz species of Cyperaceae (Poales) - Martins, Shirley [UNESP]; Scatena, Vera Lucia [UNESP] (CSIRO Publishing, 2011)
Cyperaceae possesses both non-Kranz and Kranz species, with four subtypes that differ in the number and continuity of the bundle sheaths and by presence of chloroplasts. The ontogeny of the bundle sheaths of leaves and scapes of Cyperaceae species was studied to determine primary homologies and standardise the terminology used for its description. Two non-Kranz species and 11 Kranz species from different subtypes were studied. The non-Kranz species have two bundle sheaths, with the outer one originating from the ground meristem (endodermis) and the inner one from the procambium (pericycle). Kranz species of the chlorocyperoid and eleocharoid subtypes possess two sheaths derived from the procambium (biseriate pericycle). Kranz species of the rhynchosporoid subtype have only one bundle sheath, which develops from the procambium (pericycle). Kranz species of the fimbristyloid subtype possess three bundle sheaths; the outer one originates from the ground meristem (endodermis), whereas the middle and inner ones develop from the procambium (biseriate pericycle). The outer bundle sheaths of non-Kranz and Kranz fimbristyloid species are homologues. The inner bundle sheath in non-Kranz species, the outer sheath in Kranz chlorocyperoid and eleocharoid species, the middle one in Kranz fimbristyloid species and the single sheath in Kranz rhynchosporoid species are also homologues.